2018
DOI: 10.15403/jgld.2014.1121.271.hst
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with possibly Inappropriate Histological Evaluation of Excised Specimens in Cold-snare Polypectomy for Small Colorectal Polyps

Abstract: Incomplete muscularis mucosae resection and fragmentation at retrieval are risk factors for inadequate histological evaluation of CSP-excised small colorectal polyps, especially for sessile polyps and polyps in the cecum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…The pathological unclear resected margin is often reported as incomplete resection, and this is often discussed in CSP because of its high rate. 11,[18][19][20][21] The rate of the unclear cutend of <10 mm lesions was reported to be higher in CSP than in EMR (35.6% vs. 10.1%). 10 Our study also showed that the unclear cut-end rate was not significant but higher in CSP than EMR (13.7% vs. 7.4%; Table S3).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The pathological unclear resected margin is often reported as incomplete resection, and this is often discussed in CSP because of its high rate. 11,[18][19][20][21] The rate of the unclear cutend of <10 mm lesions was reported to be higher in CSP than in EMR (35.6% vs. 10.1%). 10 Our study also showed that the unclear cut-end rate was not significant but higher in CSP than EMR (13.7% vs. 7.4%; Table S3).…”
Section: Discussionmentioning
confidence: 96%
“…The pathological unclear resected margin is often reported as incomplete resection, and this is often discussed in CSP because of its high rate 11,18–21 . The rate of the unclear cut‐end of <10 mm lesions was reported to be higher in CSP than in EMR (35.6% vs. 10.1%) 10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another cold snare polypectomy study found that 27.8% of excised polyps that were 2–14 mm in diameter did not contain muscularis mucosae, implying incomplete resection for larger polyps in the vertical margins . In addition, failure of polyp retrieval and fragmentation of small specimens during collection was associated with the effects of certain parameters on the pathological diagnosis, particularly with regard to surgical margins . Therefore, an endoscopy biomarker of effective and safe cold snare polypectomy technique needs to be established in terms of complete removal of non‐pedunculated colorectal polyps ≤10 mm.…”
Section: Future Of Cold Snare Polypectomymentioning
confidence: 99%